Kualitas semen sapi Madura setelah pengenceran dengan tris aminomethane kuning telur yang disuplementasi α-tocopherol pada penyimpanan suhu ruang - Romadhoni, Ishari; Rachmawati, Achadiah; Suyadi, Suyadi (Faculty of Animal Science, Universitas Brawijaya, 2014)
The purpose of this study was to investigate the effect of α-tocopherol in tris aminomethane extender on the quality of Madura cattle semen during storage at room temperature. Fresh semen was collected from Madura cattle bull using artificial vagina. The semen with individual motility of sperm more than 70% was used in this study. Semen was diluted with tris-aminomethane extender supplemented respectively by 0.0 mM, 0.5 mM, 1.0 mM and 1.5 mM α-tocopherol. Data were analyzed using analysis of variance. The results showed that the addition of α-tocopherol using egg yolk diluent tris aminomethane could not maintain the quality of Madura cattle semen motility, viability, abnormality and membrane integrity of spermatozoa (P>0.05) during storage at room temperature. The conclusion of the study was the addition of the antioxidant α-tocopherol into tris aminomethane egg yolk on the quality of semen had no influence (P>0.05) on individual motility, viability, abnormality and membrane integrity of spermatozoa after dilution during storage at room temperature. Keywords: Semen, α-tocopherol, Madura bull